Strategic Management of School Facilities and Infrastructure: A Case Study of State Elementary School 11 Sesetan Denpasar - I Dewa Putu Juwana; I Putu Eka Indrawan; Ni Luh Putu Yesy Anggreni (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyse the planning, implementation, and evaluation processes of facilities and infrastructure management at State Elementary School 11 Sesetan Denpasar to support the creation of an effective, comfortable, and efficient learning environment. Employing a qualitative approach with a case study design, data were collected through direct observation, in-depth interviews with school stakeholders, and document analysis. The findings show that facilities planning is carried out systematically and collaboratively, involving teachers, school leaders, and committees. The school adopts a digital inventory system to optimise asset management, while regular evaluations are conducted monthly, semiannually, and annually to ensure continuous improvement. The study concludes that structured and participatory facility management contributes significantly to improving the quality of educational services and fostering a conducive learning atmosphere. These results offer practical implications for educational policymakers and school administrators in developing adaptive and innovative school facility management strategies in response to the evolving demands of basic education.